Hamlet - Shakespear, William; Edited by Weller, Shane (New York Dover Publications, 1992)
Thought to have been written between 1599 and 1601, Hamlet relates the struggle of the individual soul set afloat on a sea of troubles and madness.
Keywords: Princes -- Drama -- Denmark -- Drama -- Hamlet -- (Legendary character) -- Drama